Biodegradação e atividade lipolítica em resíduos oleosos derivados do saneamento ambiental - Lima Junior, Amaury Freire de (2009)
Lipases (triacilglycerol acyl hydrolases, (E.C. 3.1.1.3) are enzymes, which have the ability to catalyze the hydrolysis of fats and oils in the esterification and transesterification reactions. Currently, these enzymes for the production of biodiesel, has been included as biocatalyst in the transesterification process. In the wastewater view, the biodiesel production could be converted from waste and animal fats, which they have focused on the use in enzymatic process to rendered as biodiesel feedstocks. In the present study was, therefore, to evaluate the biodegradation and lipolytic activity into microbial removal of grease-containing wastewater developed in a batch scale. The lipolytic activity was measured by spectrophotometry, aerobic respirometric methods and oils and greases contents for application in grease-trap samples from ETE-UFES, RU-UFES, UASB sludge (5% of soy oil) and frying oil. In the initial screening, 24 bacterial strains were isolated which 18 of them, capable as lipolytic bacteria, selected by Rhodamine B method. Spectrophotometric assay the lipolytic activity showed on these 18 strains a large range value of 0.02 to 3.25 U/mg of protein and the last one was strain C1, incubated with soy oil. This activity represents about 20% in commercial lipase activity. A comparision of the performances of spectrophotometric method was shown with respirometric and decay of O&G studies during that evaluation period with respective different potentials of degradation. The highest productions of CO2 was obtained in the commercial lipase AK Amano 20 (Amano Co., Japan), followed by strain “C1”, ranging from 313.64 to 1563.89 mg CO2. Strain “C1” removed 87.23% of O&G inoculated with the residue of grease-trap of ETE-UFES. Thus, respirometric methods and decay of O&G for using techniques developed for evaluating lipolytic activity were available.